The Wheat Intrinsically Disordered Protein TdRL1 Negatively Regulates the Type One Protein Phosphatase TdPP1. - Amor, Fatma; Bradai, Mariem; Zaidi, Ikram; Amorim-Silva, Vitor; Miled, Nabil; Hanin, Moez; Ebel, Chantal (MDPI, 2025)
Type 1 protein phosphatases (PP1s) are crucial in various plant cellular processes. Their function is controlled by regulators known as PP1-interacting proteins (PIPs), often intrinsically disordered, such as Inhibitor 2 (I2), conserved across kingdoms. The durum wheat TdRL1 acts as a positive regulator of plant stress tolerance, presumably by inhibiting PP1 activity. In this work, co-immunoprecipitation and bimolecular fluorescence complementation (BiFC) assays demonstrate that the durum wheat TdPP1 interacts with both TdRL1 and At-I2 in vivo. YFP fluorescence restored after TdRL1-TdPP1 interaction decorated specifically the microtubular network of the tobacco co-infiltrated cells. In vitro phosphatase assays revealed that TdRL1 inhibited the activity of wild-type TdPP1 and two mutant forms (T243M and H135A) in a concentration-dependent manner, showing a novel and potent inhibition mechanism. Structural modeling of the TdPP1-inhibitor complexes suggested that both At-I2 and TdRL1 bind to TdPP1 by wrapping their flexible C-terminal tails around it, blocking access to the active site. Remarkably, the model showed that TdRL1 differs from At-I2 in its interaction with TdPP1 by trapping the phosphatase with its N-terminal tail. These findings provide important insights into the regulatory mechanisms governing the activity of PP1s in plants and highlight the potential for targeted inhibition to modulate plant stress responses.
Keywords: Fosfoproteínas fosfatasas; Proteínas - Estructura; Type 1 protein phosphatases; Durum wheat TdRL1; PP1-interacting proteins; Phosphatase activity; Three-dimensional structure prediction